The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1111/hae.12148
|View full text |Cite
|
Sign up to set email alerts
|

Head‐to‐head comparison of the pharmacokinetic profiles of a high‐purity factor IX concentrate (AlphaNine®) and a recombinant factor IX (BeneFIX®) in patients with severe haemophilia B

Abstract: Head-on comparative studies of factor IX (FIX) concentrates performed under standardized conditions are rarely conducted regardless of being a valuable instrument guiding health care providers towards better informed and cost-effective decisions. This study is an extension of a multicentre study that assessed the efficacy, safety and pharmacokinetics (PK) of AlphaNine(®) in 25 previously treated patients with severe haemophilia B (FIX:C ≤ 2%). After a washout period ≥ 7 days following the last PK performed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 18 publications
6
19
0
Order By: Relevance
“…In the present comparative evaluation, incremental recovery was lower for Bax326 than for Immunine â infusions in both age categories, confirming the results of previous studies in which the recovery was approximately 68-86% of that expected for pdFIX concentrates [7,10,11]. Although the paediatric (<12 years) sample size in this study is not substantial, as direct comparison of pdFIX vs. rFIX has primarily been displayed in terms of PK profiles in only three cross-over studies [7,8] and one recent head-to-head comparison [26], we believe that considering the importance of IR for dose adjustment following a switch from pdFIX to Bax326, the within subjects prospective comparative analysis in patients aged >12 years will provide not only new insight but also overcome common weaknesses of between-study variability when comparing pdFIX vs. rFIX data obtained from studies with different designs and clinical settings. The same multiplication factor of 1.25 could be used for children <12 years, but the available data are limited due to the small sample size and therefore the use of the patient's individual incremental recovery is suggested.…”
Section: Parametersupporting
confidence: 88%
“…In the present comparative evaluation, incremental recovery was lower for Bax326 than for Immunine â infusions in both age categories, confirming the results of previous studies in which the recovery was approximately 68-86% of that expected for pdFIX concentrates [7,10,11]. Although the paediatric (<12 years) sample size in this study is not substantial, as direct comparison of pdFIX vs. rFIX has primarily been displayed in terms of PK profiles in only three cross-over studies [7,8] and one recent head-to-head comparison [26], we believe that considering the importance of IR for dose adjustment following a switch from pdFIX to Bax326, the within subjects prospective comparative analysis in patients aged >12 years will provide not only new insight but also overcome common weaknesses of between-study variability when comparing pdFIX vs. rFIX data obtained from studies with different designs and clinical settings. The same multiplication factor of 1.25 could be used for children <12 years, but the available data are limited due to the small sample size and therefore the use of the patient's individual incremental recovery is suggested.…”
Section: Parametersupporting
confidence: 88%
“…This is the reason why lower values of AUC, higher clearance and shorter half‐life have been reported with respect to the outcomes of our study. On the contrary, when the sampling time was prolonged up to 72 h , the PK outcomes resulted very similar to ours. The average values of all clearances observed in our study resulted 50% less than those reported in previous comparative studies of N9‐GP or rFIX‐FP because of different AUC.…”
Section: Discussionmentioning
confidence: 99%
“…The average values of all clearances observed in our study resulted 50% less than those reported in previous comparative studies of N9‐GP or rFIX‐FP because of different AUC. The clearance observed in this study is similar to that of rFIX‐Fc . In addition, the Vss was quite small compared with the large Vss of rFIX‐Fc, whose mean value was 250 mL kg −1 .…”
Section: Discussionmentioning
confidence: 99%
“…From March 2013 to July 2014, eight (19.0%) of the 42 so far unpublished RT were published in 10 JA. Published trials on new factor IX products comprised NCT01027364 , NCT01361126 , NCT00093210 , NCT01128881, NCT01174446 and NCT01488994 with several publications , of which one relates to HRQoL , and NCT01507896 on surgery with a new factor IX product . A first randomized study comparing on‐demand treatment with two prophylaxis regimens in haemophilia B patients trial NCT00364182 was published as well .…”
Section: Discussionmentioning
confidence: 99%